2006
DOI: 10.1002/jcu.20226
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged lymph nodes in porta hepatis: Sonographic sign of chronic hepatitis B and C infections

Abstract: Lymph nodes in the hepatoduodenal ligament, especially those wider than 5 mm, suggest chronic HBV or HCV infection instead of only chronic hepatitis, especially in an endemic area such as Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
9
1
1
Order By: Relevance
“…None of those studies, however, were powered adequately to examine such an association; in one study, only 23 patients with cirrhosis were examined and in the second only five. On the other hand, there is indirect support for our conclusion from studies that found that HCV-infected patients with higher fibrosis scores were more likely to have PLNE [12][13][14][15]. In addition, PLNE is highly prevalent among cirrhotic patients, including among those with HCV infection and cirrhosis [29].…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…None of those studies, however, were powered adequately to examine such an association; in one study, only 23 patients with cirrhosis were examined and in the second only five. On the other hand, there is indirect support for our conclusion from studies that found that HCV-infected patients with higher fibrosis scores were more likely to have PLNE [12][13][14][15]. In addition, PLNE is highly prevalent among cirrhotic patients, including among those with HCV infection and cirrhosis [29].…”
Section: Discussioncontrasting
confidence: 42%
“…However, in some of the studies that used ultrasonography for detection of PLNE, the prevalence of PLNE has been higher [12,13]. The differences could be explained by methodological differences and criteria used to detect PLNE.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In particular, hepatic hilum lymph nodes may enlarge not only in malignant conditions but also in benign disorders such as viral hepatitis. It has also been reported that assessing the number and size of swollen lymph nodes can be reflected in matters such as determining the effectiveness of treatment [15][16][17]. In the present study, enlarged hepatic hilum lymph nodes were detected in 31 of 120 patients.…”
Section: Enlarged Hepatic Hilum Lymph Nodessupporting
confidence: 39%
“…Lymphadenopathy is not specific for acute hepatitis and is also reported in chronic HCV and HBV infections [19].…”
Section: Ultrasound Scan and Acute Hepatitis Cmentioning
confidence: 99%